Truth is the arrow, mercy is the bow : a DIY manual for the construction of stories - Almond, Steve (Zando, 2024)
"In Truth Is the Arrow, Mercy Is the Bow, Steve Almond employs the radical empathy he displayed as co-host (with Cheryl Strayed) of the podcast Dear Sugars to explore the joys and trials of storytelling, and to explode the myths that hold us back from writing our deepest and truest work. The book includes chapters on plot, character, and chronology, but travels far beyond the earnest intentions of most craft books. It includes essays on humor, sex, writer's block, and the dividends of failure, as well as prompts to generate new work and a rollicking Frequently Asked Questions section. You'll never think about writing the same way again."--Back cover.